Drywood Pest Termite Cryptotermes brevis (Blattaria: Isoptera: Kalotermitidae): a Detailed Morphological Study of Pseudergates - Cesar, C. S.; Giacometti, D.; Costa-Leonardo, A. M. [UNESP]; Casarin, F. E. (Springer Nature, 2019)
The Kalotermitidae Cryptotermes brevis (Walker) presents colonies that lack a true worker caste. They have totipotent worker-like individuals named pseudergates. Few studies have characterized the morphology of immature instars, including pseudergates. In order to identify these instars and characterize the pseudergates, we conducted a comparison between morphometric and morphological variations among immature individuals of C. brevis colonies. Juvenile hormone analog (JHA) was used in the first instar nymphs to induce regressive molts and compare morphological differences between nymphs and pseudergates. Results showed the existence of three larval instars and four nymphal instars. These immatures were morphologically characterized. Individuals classified as third instar larvae presented white body, 10 to 12 antennal articles, absent or small non-pigmented compound eyes, and absence of wing buds. Pseudergates presented pigmented abdomen and sclerotized cuticle, 10 to 12 antennal articles, and absent or small compound eyes, and few specimens had large pigmented compound eyes and absence of wing buds. First instar nymphs had pigmented abdomen and sclerotized cuticle, 10 to 12 antennal articles, both large non-pigmented and pigmented compound eyes, the presence of wing buds. Bioassays using JHA on first instar nymphs resulted in a large percentage of nymph-soldier intercastes. We concluded that abdomen pigmentation and sclerotized cuticle are good characters to differentiate pseudergates from larvae and the absence of wing buds is a good character to differentiate pseudergates from nymphs. Our findings not only contribute to the basic biological and morphological information of this species but also help to identify correctly pseudergates in further studies that involve applied bioassays.
Keywords: Drywood termite; false worker; juvenile hormone analog; pest insect; polyphenism; totipotent individuals